The Compatibility of Speaking Politeness Introduced in Conversation Texts in MTs English Textbook Grade VIII With The Standard of Content - Ulin Nuha (Lembaga Pendidikan Hikmatun Najah Blora, 2025)
This study focuses on the issues: social contextual factors approach which analyzes the participants in the interaction and the communicative situation and politeness which analyzes the respect that an individual has for himself or herself, and maintaining the